Simultaneous Determination of Amlodipine and Valsartan in Tablet By UV Spectrophotometry With Successive Ratio Method - P, Nia N.; S, Siti M; P, Muchlisyam (Asian Journal of Pharmaceutical Research and Development, 2021)
Objectives: This study aims to develop a spectrophotometric method by successive ratio method in simultaneous determination of AML and VLS on tablet preparations without separation. Methods: This study aims to develop a spectrophotometric method by successive ratio method in simultaneous determination of AML and VLS on tablet preparations without separation and then tested for validity based validation parameters, namely linearity, accuracy, precision, LOD and LOQ and intraday and interday. Then, this method was applied to determine the levels of AML and VLS on dosage tablet. Result: Manipulating the ratio spectra of the binary mixture allowed their determination at 358,4 nm and 247,4 nm and in the concentration ranges of (4-12 µg/mL) and (6-18 µg/mL) for amlodipine and valsartan, respectively Conclusion: The successive ratio method can be used to determine the levels of a mixture of amlodipine and valsartan drugs.